Lactation‐induced reduction in hippocampal neurogenesis is reversed by repeated stress exposure. Issue 6 (19th February 2014) - Hillerer, Katharina M.; Neumann, Inga D.; Couillard‐Despres, Sebastien; Aigner, Ludwig; Slattery, David A.
ABSTRACT The peripartum period is a time of high susceptibility for mood and anxiety disorders, some of which have recently been associated with alterations in hippocampal neurogenesis. Several factors including stress, aging, and, perhaps unexpectedly, lactation have been shown to decrease hippocampal neurogenesis. Intriguingly, lactation is also a time of reduced stress responsivity suggesting that the effect of stress on neurogenic processes may differ during this period. Therefore, the aim of the present study was to assess the effect of repeated stress during lactation [2 h restraint stress from lactation day (LD) 2 to LD13] on brain weight, hippocampal volume, cell proliferation and survival, and on neuronal and astroglial differentiation. In addition to confirming the known lactation‐associated decrease in cell proliferation and survival, we could reveal that stress reversed the lactation‐induced decrease in cell proliferation, while it did not affect survival of newly born cells, nor the number of mature neurons, nor did it alter immature neuron production or the number of astroglial cells in lactation. Stress exposure increased relative brain weight and hippocampal volume mirroring the observed changes in neurogenesis. Interestingly, hippocampal volume and relative brain weight were lower in lactation as compared to nulliparous females under nonstressed conditions. This study assessed the effect of stress during lactation on hippocampal neurogenesis and indicates that stress interferes with important peripartum adaptations at the level of the hippocampus. © 2014 Wiley Periodicals, Inc.